The communicativeness of English tests at vocational high school - Albiansyah; Agam Prasetyo; Minkhatunnakhriyah (TRANSBAHASA, 2020)
Language testing and assessment play a crucial role in evaluating the school quality system and in regarding the progress of student’s achievement. Since most classrooms in Indonesia consist of more than 30 to 40 students in a classroom, it is not an easy task to handle and to assess the educational success of students. It is very important to assess the achievement of the students. Further, teachers without standardized assessments will not understand the experience, skills, and abilities of the students in their classroom. The aim of this article is to examine the content of mid-term exams that were given to class 10 in the second semester of the 2019 – 2020 academic year. The objective of the article is to find out the content of the English test measured the communicative competence of students. There were five tests collected from five schools in different clusters of South Tangerang, Indonesia. The results of analysis showed that the tests were failed in measuring the student’s communicative competence while language focus could be tested by them.